2016
DOI: 10.1590/0037-8682-0437-2015
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell lymphotropic virus-1 infection: three infected generations in the same family

Abstract: The human T-cell lymphotropic virus-1 (HTLV-1) affects worldwide population; the estimated number of currently infected individuals is 10-20 million. In this report, we describe the clinical findings of three family members with vertical transmission of HTLV-1. This case report highlights the importance of healthcare providers who have optimal knowledge about HTLV-1 including its transmission and pertinent attributes, and who are able to provide affected individuals with adequate information regarding their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Ueno et al (2012) reported that adult ACs infected by MTCT had higher PVL (2.41 copies of HTLV-1 pX gene/100 PBMC) than those infected by sexual intercourse (0.34 copies of HTLV-1 pX gene/100 PBMC), however the time from infection was not evaluated in this study (Ueno et al, 2012). This supports the hypothesis that vertical transmission can be associated with high risk of HTLV-1 associated disease onset, which could contribute to explain some high prevalence of disease among certain family members (Pombo-De-Oliveira et al, 2001; da Silva et al, 2013; Alvarez et al, 2016; Mendes et al, 2016). Exposure to HTLV-1 at the beginning of life has been associated with a higher risk of ATL (Hisada et al, 1998, 2001; Kannagi et al, 2004).…”
Section: Neonatal Infection and The Risk Of Disease Developmentsupporting
confidence: 85%
See 1 more Smart Citation
“…Ueno et al (2012) reported that adult ACs infected by MTCT had higher PVL (2.41 copies of HTLV-1 pX gene/100 PBMC) than those infected by sexual intercourse (0.34 copies of HTLV-1 pX gene/100 PBMC), however the time from infection was not evaluated in this study (Ueno et al, 2012). This supports the hypothesis that vertical transmission can be associated with high risk of HTLV-1 associated disease onset, which could contribute to explain some high prevalence of disease among certain family members (Pombo-De-Oliveira et al, 2001; da Silva et al, 2013; Alvarez et al, 2016; Mendes et al, 2016). Exposure to HTLV-1 at the beginning of life has been associated with a higher risk of ATL (Hisada et al, 1998, 2001; Kannagi et al, 2004).…”
Section: Neonatal Infection and The Risk Of Disease Developmentsupporting
confidence: 85%
“…Early after the first identification of HTLV-1 the possibility of mother-to-child transmission (MTCT) was supported by several pieces of evidence including: (1) high incidence of HTLV-1 infection in children born to HTLV infected mothers; (2) high prevalence of infection in mothers of HTLV-1 seropositive children; (3) presence of approximately 10 3 cells infected with HTLV/mL in milk from carrier mothers; (4) experimental infection in animals using fresh milk cells from HTLV-1 infected women (Hino, 2011); (5) low transmission risk among bottle-fed children when comparing to breast fed; and more recently reduced incidence of infection after implementation of antenatal screening and avoidance of breastfeeding observed in Japan. Thus, this route of infection is well stablished and is responsible for the maintenance of HTLV-1 in several generations of the same family (The T and B-cell malignancy study group, 1988; Plancoulaine et al, 1998; Catalan-Soares et al, 2005; da Costa et al, 2013; Mendes et al, 2016). Moreover, transmission is known to be associated with the risk of adult T-cell leukemia (ATL), a highly aggressive and usually fatal malignancy caused by HTLV-1.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that, preventing the occurrence of a single new case, it is possible to inhibit the transmission chain of this individual, blocking virus maintenance for generations and intra-family dissemination, a fact commonly observed in HTLV infection [8,9,5254]. In Salvador, 32.56% of the family members of the HTLV-1 seropositive women were positive, including children from previous pregnancy [55].…”
Section: Discussionmentioning
confidence: 99%
“…International and national studies have proven the high infection prevalence among families with virus carriers, especially in endemic areas [12,13]. Intrafamily transmission has a rate 18 times higher than transmission in the general population [5].…”
Section: Introductionmentioning
confidence: 99%